Pengaruh Kesadaran Merek dan Citra Merek Terhadap Keputusan Pembelian di Kopi Tengah, Blok M, Jakarta Selatan - Junandar, Dwi Rifki; Chairani, Alda; Ingkadijaya, Rahmat (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan Digital, 2026)
This study aims to analyze the influence of Brand Awareness and Brand Image on the Purchase Decision of consumers at Kopi Tengah Blok M. The study employed a quantitative approach. Data were collected through questionnaires distributed to consumers of Kopi Tengah Blok M who were selected using purposive sampling. The research instrument used a five-point Likert scale, and the data were analyzed using multiple linear regression with the assistance of SPSS. The research instrument was tested through validity and reliability tests, while hypothesis testing was conducted using partial and simultaneous tests to examine the effects of each independent variable and their combined effect on Purchase Decision. The results show that Brand Awareness has a positive and significant effect on Purchase Decision. Brand Image also has a positive and significant effect on Purchase Decision. Furthermore, Brand Awareness and Brand Image simultaneously have a significant effect on Purchase Decision. These findings indicate that the better consumers recognize and recall the brand and the more positive their perceptions of Kopi Tengah are, the greater their tendency to make a purchase. This study provides practical implications for Kopi Tengah to strengthen brand awareness and brand image as part of its marketing strategy to increase consumer purchase decisions. Keywords: brand awareness, brand image, purchase decision, coffee shop